Proyecto de inversión para la creación de unrestaurante de comida china tradicional en la ciudad de Guayaquil - Castro Maldonado, Víctor Xavier (2009)
This project performs an anlysis to determine the poddibility of making an investment in the creation of a traditional Chinese food restaurant in the city of Guayaquil